2020
DOI: 10.24843/jchem.2020.v14.i02.p13
|View full text |Cite
|
Sign up to set email alerts
|

ANTIOXIDANT AND INHIBITION OF ALPHA-AMYLASE ACTIVITIES OF PAPASAN (Coccinia grandis (L.) Voigt) LEAVES AND BELIMBING WULUH (Averrhoa bilimbi L.) FRUITS COMBINED INFUSIONS

Abstract: The pharmacology activity of an herb can be increased by combining it with other herbs. This study aimed to make herbal infusions from the combination of papasan (Coccinia grandis (L.) Voigt) leaves and belimbing wuluh (Averrhoa bilimbi L.) fruits. Antioxidant and inhibition properties of alpha-amylase enzymes were then tested. A mixture of Coccinia grandis (L.) Voigt leave and Averrhoa bilimbi L. fruit powder with a mass ratio of 1:3, 1:1, and 3:1 was brewed with 100 mL of boiling water for 5 minutes. The mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a study conducted by Pulbutr et al ( 7 ), the aqueous leaf extract of C. grandis was observed to have a significant inhibitory effect on the α-amylase enzyme, as evidenced by an IC 50 value of (8.1±0.7) µg/mL. In another study, Putra et al ( 49 ) observed that the plant sample showed the strongest inhibition of α-amylase activity, with the lowest half maximal inhibitory concentration (IC 50 =0.8±0.4 mg/mL). Packirisamy and Sivaprakasam ( 50 ) reported that the fruit extract of C. grandis showed significant inhibitory effect on α-amylase.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In a study conducted by Pulbutr et al ( 7 ), the aqueous leaf extract of C. grandis was observed to have a significant inhibitory effect on the α-amylase enzyme, as evidenced by an IC 50 value of (8.1±0.7) µg/mL. In another study, Putra et al ( 49 ) observed that the plant sample showed the strongest inhibition of α-amylase activity, with the lowest half maximal inhibitory concentration (IC 50 =0.8±0.4 mg/mL). Packirisamy and Sivaprakasam ( 50 ) reported that the fruit extract of C. grandis showed significant inhibitory effect on α-amylase.…”
Section: Resultsmentioning
confidence: 93%
“…In another study, Putra et al (48) observed that the plant sample exhibited the most potent inhibition of α-amylase activity, with the lowest half-inhibitory concentration (IC50 = 0.75±0.45 mg/mL). Packirisamy and Sivaprakasam (49), reported that the fruit extract of C. grandis exhibited a significant inhibitory effect on α-amylase.…”
Section: Evaluation Of the Inhibitory Capacity Of C Grandis Leaf Extr...mentioning
confidence: 95%